Servlets and JSP Tutorial for Beginners - T, Karthikeya (Packt Publishing, 2021)
Enter the world of J2EE by learning servlets and JSP technologies the easy way About This Video Gain knowledge about servlets and JSPs to enter the world of JavaEE Understand JSP action elements and create custom tags Understand socket communication through TCP/IP, UDP, broadcasting, and more through examples In Detail Servlets and JSP are the backbone of all modern-day web applications. In this course, we will start by talking about some network components and understand the basics of networking with simple real-world examples. And then, we will jump into some good examples on network programming. Here, we will take examples of socket communication through TCP/IP, UDP, Broadcasting, Multicasting, and many more examples. By now, you will have gained foundational knowledge to explore servlets and JSPs and to enter the world of JavaEE. Learning about servlets and JSP lays a great foundation for learning all modern-day frameworks. This course is almost like a prerequisite to learning modern-day Java frameworks as they internally rely on these technologies. This course will surely make your Java journey smooth without any glitches. We will start by talking about the basics of servlets and JSP with some good example programs and cover everything that you need to know on servlet and JSP technologies.